Peak oxygen uptake in Paralympic sitting sports: A systematic literature review, meta- and pooled-data analysis - Baumgart, J. K.; Brurok, B.; Sandbakk, O. (PLOS ONE, 2018)
Peak oxygen uptake (VO2peak) in Paralympic sitting sports athletes represents their maximal ability to deliver energy aerobically in an upper-body mode, with values being influenced by sex, disability-related physiological limitations, sport-specific demands, training status and how they are tested. Objectives: To identify VO2peak values in Paralympic sitting sports, examine between-sports differences and within-sports variations in VO2peak and determine the influence of sex, age, body-mass, disability and test-mode on VO2peak. Design: Systematic literature review and meta-analysis. Data sources: PubMed, CINAHL, SPORTDiscusTM and EMBASE were systematically searched in October 2016 using relevant medical subject headings, keywords and a Boolean. Eligibility criteria: Studies that assessed VO2peak values in sitting sports athletes with a disability in a laboratory setting were included. Data synthesis